Accessory-free quantitative smartphone imaging of colorimetric paper-based assays. Issue 11 (2nd May 2019) - Kong, Tian; You, Jae Bem; Zhang, Biao; Nguyen, Brian; Tarlan, Farhang; Jarvi, Keith; Sinton, David
Abstract : We show an accessory-free smartphone-based imaging method applicable to different lighting conditions and correct for differences in phone models. Abstract : The combination of smartphone technology and colorimetric paper-based microfluidics can enable simple, inexpensive diagnostics. However, imaging colorimetric diagnostic results via smartphones currently requires accessories to mitigate the influence of variability in surrounding lighting conditions. Here, we present an accessory-free smartphone-based colorimetric imaging method that enlists the built-in LED light source to dominate ambient lighting in combination with background and colour rescaling. This simple approach enables quantitative measurements from paper-based tests by compensating for different environmental lighting conditions and is universally applicable with respect to phone models and manufacturers. We demonstrate the method with three dominant phone makes and models in a cell counting application with a paper-based yeast detection device. The detection results are in good agreement with cell counting using automated cell counters. Eliminating the need for make/model specific accessories, this approach helps realize the potential for low-cost, broadly applicable paper-based diagnostics.